The consent to the imposition in global taxation - Farri, Francesco (2019)
The international economic field of nations has undergone accelerated changes from the end of the 20th century to the present day. The economic isolationism characteristic of centuries before ours has been left in the past. International institutions take a key role in making international tax decisions, as well as at the national level. In the first instance, the author reviews and questions the democratic foundations on which the taxation of international organizations towards States is established in times of the digital economy. Furthermore, the article analyzes the concepts of legitimacy and soft law, as well as the principles of consent to the imposition and saving clause. In a second instance, the phenomena of tax avoidance and evasion inevitably produced by the differences between the various taxation systems and, consequently, the centrality of the state against the personal tax as the best redistributive policy model is examined.